2021
DOI: 10.3390/diagnostics11030384
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Extracellular Vesicles from Biological Fluids via the Aggregation–Precipitation Approach for Downstream miRNAs Detection

Abstract: Extracellular vesicles (EVs) have high potential as sources of biomarkers for non-invasive diagnostics. Thus, a simple and productive method of EV isolation is demanded for certain scientific and medical applications of EVs. Here we aim to develop a simple and effective method of EV isolation from different biofluids, suitable for both scientific, and clinical analyses of miRNAs transported by EVs. The proposed aggregation–precipitation method is based on the aggregation of EVs using dextran blue and the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…A variant of optimization the PEG precipitation technique that allows obtaining more "pure" exosome preparations is described in [55]. The authors suggested enriching the sample with membrane vesicles before adding PEG.…”
Section: Precipitation Techniquesmentioning
confidence: 99%
“…A variant of optimization the PEG precipitation technique that allows obtaining more "pure" exosome preparations is described in [55]. The authors suggested enriching the sample with membrane vesicles before adding PEG.…”
Section: Precipitation Techniquesmentioning
confidence: 99%
“…Precipitation-based isolation is inexpensive, requires no special equipment, and is compatible with both low-and highsample volumes. Nevertheless, this method suffers from co-isolation of non-EV particles and protein complexes and must be further improved [57].…”
Section: Methodological Approaches To Study Rna Molecules Carried By Evsmentioning
confidence: 99%
“…EVs that are regularly secreted by normal cells into the extracellular space can be recovered in many if not all biological fluids [16,17]. More importantly, specific cancer-cellderived EVs are released into the extracellular space and can be found in plasma, serum, and urine of tumor-bearing patients.…”
Section: Isolation and Characterization Of Evs For The Diagnosis Of Gynecological And Genitourinary Malignanciesmentioning
confidence: 99%
“…Ultracentrifugation (UC), density gradient centrifugation (DC), precipitation, immunoaffinity capture, size exclusion chromatography (SEC), and microfluidic-based isolation are the most relevant EV isolation procedures for patients with suspected cancer [17,18]. UC has historically been regarded as the gold standard for EV isolation in basic and translational research.…”
Section: Isolation and Characterization Of Evs For The Diagnosis Of Gynecological And Genitourinary Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation